Os indesejáveis: agentes públicos e a gestão da mobilidade de trecheiros e pessoas em situação de rua - Freitas, Cledione Jacinto [UNESP] (2014)
The state officials attention given to roamers and people on the streets is becoming increasingly subsidized by an arsenal of standards, guidelines, strategies, institutions, professional, political, to account for the various facets of nomadic and city life. For this reason, the research aimed to investigate how these officials responsible for public welfare office dealt with roamers and people on the streets and conceived this way of life. Imported mainly identify practices and interventions in roamers way of life and people on the streets seeking to disqualify the nomadism that took as a reprehensible way of life or that generated suffering and therefore, needed to be avoided. Interested also understand how, by the look of professional social work, produces the figure of the undesirable from abroad, that needs to be moved to other spaces through public assistance policies. The research took place in a city of approximately one hundred thousand inhabitants in the western region of São Paulo. This city is located in an important roamers circulation corridor formed by the intersection of trunk roads linking the north of the state to the Paraná and the west of the State to the eastern region, which is the capital. The methodology used was ethnography in Psychology with participant observation. We follow the work of the city's team, made up of social workers, psychologists and mid-level employees, crowded in Social Reference Center of Specialized Assistance (CREAS) and the Migrant Assistance Unit (UAM), and other professionals who participated the Working Group on Homelessness or who were involved with the issue of care of nomadism, and townspeople who were present and participated directly and indirectly in the search, allowing observe the practices and discourses that are construct for roamers who come in town and people on the streets who insist on staying in the squares. The program took place...